Trade off between stubble management and ecosystem services - KUMAR, Shiv; Abdulla, Abdulla; Singh, Chhatra Pal (Indian Farming, 2020)
Right to clean air is a part of right to life which is a fundamental right enshrined in the constitution of India. Clean air is the most important element of a healthy life. Pollution is a public bad that emanates from a side effect of economic activities, providing us with good things and services. Production and consumption activities generate pollution and waste, and atmospheric environment can absorb pollution/waste up to a limit. According to Green Peace report of the year 2017, severe air pollution is not a problem restricted to Delhi-NCR (National Capital Region). It is a national problem that is killing 1.2 million Indians every year and costing the economy an estimated 3% of GDP. If the country’s development is important, fighting air pollution has to be a priority.